Minority of Male Teachers in Kindergartens as a Result of Gender Stereotypes in Society - Nur Rohmah; Fahri Hidayat (Edumaspul: Jurnal Pendidikan, 2023)
The phenomenon of the minimum number of male kindergarten teachers is increasingly visible in Indonesia, so that people increasingly think that kindergarten teachers are a woman's profession. This results in an imbalance of gender roles in Kindergarten. Discussion of gender-related issues in kindergarten is considered too commonplace and often escapes society's attention. The aim of this research is to describe and analyze gender stereotypes which result in a minority of male teachers in kindergarten. Not only that, this research also provides an alternative view of the role of a man as a teacher in kindergarten. This research is a literature study that uses a qualitative approach. The results of this research are stereotypes that grow and develop in society regarding male kindergarten teachers, including; firstly, kindergarten teachers are attached to feminine traits, while men are attached to masculine traits, secondly, the assumption is that male kindergarten teachers are "gay", thirdly, the kindergarten profession which is not financially promising is not suitable for men who are charged with the role of "backbone", fourth, men must have challenging work, while the profession of kindergarten teacher is a profession that is not challenging and has low risk.